Brain tuberculoma in a non-endemic area - Robert M. Lober; Anand Veeravagu; Harminder Singh (MDPI AG, 2013)
Brain tuberculoma has previously accounted for up to a third of new intracranial lesions in areas endemic with tuberculosis, but is unexpected in the United States and other Western countries with improved disease control. Here we show the importance of considering this diagnosis in at-risk patients, even with no definitive pulmonary involvement. We describe a young man who presented with partial seizures and underwent craniotomy for resection of a frontoparietal tuberculoma. He subsequently completed six months of antituberculosis therapy and was doing well without neurological sequelae or evidence of recurrence five months after completion of therapy. With resurgence of tuberculosis cases in the United States and other Western countries, intracerebral tuberculoma should remain a diagnostic consideration in at-risk patients with new space occupying lesions. Mass lesions causing neurological sequelae can be safely addressed surgically and followed with antituberculosis therapy.